Wings of fire: an autobiography - Kalam, A.P.J. Abdul; Tiwari, Arun (India, Universities Press, 1999)
An Autobiography is the story of India's 11th president, Abdul A.P.J. Kalam, and his rise from an obscure background to the power-filled corridors of Rashtrapati Bhavan. The book is a narration of his life from his humble beginnings to the start of his professional life and finally to him becoming the president of India. The autobiography is narrated through four chapters-Orientation, Creation, Propitiation and Contemplation. Kalam's story begins in a small, impoverished village in Rameswaram, Tamil Nadu and goes on to detail his work at NASA and other US institutions. With Kalam's return to India the book elaborates on his label as the 'Missile Man of India'. While focusing on the years between 1981 and 1991 the authors reveal the details of as the Agni, Prithvi, Akash, Trishul and Nag missiles. It ends with strikingly in depth look at his philosophy and his legacy.
Keywords: Abdul Kalam; Autobiography; Physics